Alterations of the MT-ATP8 Gene and 9-bp Deletion in Vietnamese Patients with Breast Cancer - Thi Tu Linh, Nguyen; Thao, Nguyen Thi; Dung, Do Thi; Thai, Trinh Hong (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 1DO - 10.25073/2588-1140/vnunst.4713, 2018)
The MT-ATP8 gene encodes for A6L protein subunit belonging to the proton channel of the ATP synthase. MT-ATP8 gene’s mutations can affect the structure and function of the ATP synthase, which may cause diseases. In this study, alterations of MT-ATP8 gene were investigated in tumor tissues of patients with breast cancer and control blood samples using PCR combined with direct sequencing and PCR-RFLP methods, data were analyzed using bioinformatics tools and statistical methods. Sequencing results revealed 5 variants of MT-ATP8 gene on 35 breast tumor tissues and 26 blood samples of controls, of which two mutations C8414T and C8417T altered the amino acid sequence of the resulting protein. The C8417T was further screened by PCR-RFLP and was found in 0,98% (1/102) of breast tumor samples. This change lead to substitution of lecine to phenylalanine (L18F) in a highly conserved position of A6L and was predicted as probably damaging to the structure and function of the protein. Additionally, a 9 bp deletion was also observed in a non-coding region of mtDNA in 26,5% (27/102) of breast cancer patients and 27% (7/26) of controls. Thus, these results showed that C8417T variant in the conserved position of MT-ATP8 gene was rare and first identified in a group of breast cancer patients in Vietnam. Keywords Breast cancer, mitochondrial DNA, MT-ATP8 References [1] Petros JA, Baumann AK, Ruiz-Pesini E, Amin MB, Sun CQ, Hall J, Lim S, Issa MM, Flanders WD, Hosseini SH, Marshall FF, Wallace DC, mtDNA mutations increase tumorigenicity in prostate cancer, Proc Natl Acad Sci U S A (2005), 102(3):719-24. [2] Wang X, The expanding role of mitochondria in apoptosis, Genes Dev (2001), 15(22):2922-33. [3] Jonckheere AI, Smeitink JA, Rodenburg RJ, Mitochondrial ATP synthase: architecture, function and pathology, J Inherit Metab Dis (2012), 35(2):211-25. [4] Grzybowska-Szatkowska L, Slaska B, Rzymowska J, Brzozowska A, Florianczyk B, Novel mitochondrial mutations in the ATP6 and ATP8 genes in patients with breast cancer, Mol Med Rep (2014), 10(4):1772-8. [5] Adzhubei IA, Schmidt S, Peshkin L, Ramensky VE, Gerasimova A, Bork P, Kondrashov AS, Sunyaev SR, A method and server for predicting damaging missense mutations, Nat Methods (2010), 7(4):248-9. [6] Thapa S, Lalrohlui F, Ghatak S, Zohmingthanga J, Lallawmzuali D, Pautu JL, Senthil Kumar N, Mitochondrial complex I and V gene polymorphisms associated with breast cancer in mizo-mongloid population, Breast Cancer (2016), 23(4):607-16. [7] Warburg O, On the origin of cancer cells, Science (1956), 123:309-14. [8] Dumas JF, Rousse D, Servais S, Mitochondria and cancer, Cellular Bioenergetics in Health and Diseases: New Perspectives in Mitochondrial Biology (2012), 115-47. [9] Mkaouar-Rebai E, Kammoun F, Chamkha I, Kammoun N, Hsairi I, Triki C, Fakhfakh F, A de novo mutation in the adenosine triphosphatase (ATPase) 8 gene in a patient with mitochondrial disorder, J Child Neurol (2010), 25(6):770-5. [10] Jonckheere AI, Hogeveen M, Nijtmans LG et al., A novel mitochondrial ATP8 gene mutation in a patient with apical hypertrophic cardiomyopathy and neuropathy, J Med Genet (2008), 45:129-33. [11] Ware SM, El-Hassan N, Kahler SG et al., Infantile cardiomyopathy caused by a mutation in the overlapping region of mitochondrial ATPase 6 and 8 genes, J Med Genet (2009), 46:308-14. [12] Liu VW, Shi HH, Cheung AN, Chiu PM, Leung TW, Nagley P, Wong LC, Ngan HY, High incidence of somatic mitochondrial DNA mutations in human ovarian carcinomas, Cancer Res (2001), 61(16):5998-6001. [13] Zhuo G, Feng G, Leng J, et al., A 9-bp deletion homoplasmy in women with polycystic ovary syndrome revealed by mitochondrial genome-mutation screen, Biochem Genet (2010), 48:157-163. [14] Abu-Amero KK, Alzahrani AS, Zou M, Shi Y, Association of mitochondrial DNA transversion mutations with familial medullary thyroid carcinoma/multiple endocrine neoplasia type 2 syndrome, Oncogene (2006), 25:677-84. [15] Bonora E, Porcelli AM, Gasparre G, et al., Defective oxidative phosphorylation in thyroid oncocytic carcinoma is associated with pathogenic mitochondrial DNA mutations affecting complexes I and III, Cancer Res (2006), 66:6087-96. [16] Costa-Guda J, Tokura T, Roth SI, Arnold A, Mitochondrial DNA mutations in oxyphilic and chief cell parathyroid adenomas, BMC Endocr Disord (2007); 7:8. [17] Chintha R, Kaipa PR, Sekhar N, Hasan Q, Mitochondria and tumors: A new perspective, Indian J Cancer (2013), 50(3). [18] Tan DJ, Bai RK, Wong LJ, Comprehensive scanning of somatic mitochondrial DNA mutations in breast cancer, Cancer Res (2002), 62(4):972-6. [19] Tipirisetti NR, Lakshmi RK, Govatati S, Govatati S, Vuree S, Singh L, Raghunadha Rao D, Bhanoori M, Vishnupriya S, Mitochondrial genome variations in advanced stage breast cancer: a case-control study, Mitochondrion (2013), 13(4):372-8. [20] Ghaffarpour M, Mahdian R, Fereidooni F, Kamalidehghan B, Moazami N, Houshmand M, The mitochondrial ATPase6 gene is more susceptible to mutation than the ATPase8 gene in breast cancer patients, Cancer Cell Int (2014), 14(1):21. [21] Perucca-Lostanlen D, Narbonne H, Hernandez JB, et al., Mitochondrial DNA variations in patients with maternally inherited diabetes and deafness syndrome, Biochem Biophys Res Commun (2000), 277(3):771-5. [22] Bai Y, Guo Z, Xu J, Zhang J, Cui L, Zhang H, Zhang S, The 9-bp deletion at position 8272 in region V of mitochondrial DNA is associated with renal cell carcinoma outcome, Mitochondrial DNA A DNA Mapp Seq Anal (2014), 27(3):1973-5. [23] Jin Y, Yu Q, Zhou D, Chen L, Huang X, Xu G, Huang J, Gao X, Gao Y, Shen L, The mitochondrial DNA 9-bp deletion polymorphism is a risk factor for hepatocellular carcinoma in the Chinese population, Genet Test Mol Biomarkers (2012), 16(5):330-4. [24] Ren W, Li Y, Li R, Feng H, Wu S, Mao Y, Huang L, Mitochondrial intergenic COII/tRNA(Lys) 9-bp deletion, a biomarker for hepatocellular carcinoma? Mitochondrial DNA A DNA Mapp Seq Anal (2015), 27(4):2520-2. [25] Cortopassi GA, Shibata D, Soong NW, Arnheim N, A pattern of accumulation of a somatic deletion of mitochondrial DNA in aging human tissues, Proc Natl Acad Sci U S A (1992), 89(16):7370-4.